CORRECTION CHRONIC ISCHEMIA FINITE COMBINATION OF VARDENAFIL AND PENTOXIFYLLINE EXPERIMENT - K. I. Lavrinenko; A. S. Belous; G. S. Mal; E. B. Artyushkova; E. A. Loyko (Кубанский научный медицинский вестник, 2016)
Experimental work conducted on Wistar rat line. Ischemia was simulated on the shin muscles of rats. Muscle ischaemia correction performed intragastric administration of pentoxifylline at a dose of 60 mg / kg of vardenafil dose of 0.9 mg / kg daily for 28 days and in combination vardenafil dose of 0.09 mg / kg of pentoxifylline and 30 mg / kg for 7 days. Results were evaluated 21 and 28 hours. The level of microcirculatory perfusion expressed in units. Correction of muscle ischemia combination of vardenafil and pentoxifylline in small doses for 7 days stimulates angiogenesis and improves blood circulation in the distal extremities in proportion to the average therapeutic dose of vardenafil 28 days.